The Psychological Conflict of the Main Character and the Value of Character Education in the Novel Shoes Dahlan by Khrsna Pabichara and its Relevance to Indonesian Language Learning in Elementary Schools (Study of Literary Psychology) - Rahayu, Rika (International Conference on Elementary Education, 2022)
The purpose of this study is to find out the psychiatric conflicts of the main characters and the value of character education in Khrisna Pabichara's Shoe Dahlan Novel. Research methods use descriptive qualitative shorts. The result of this study is that there are values ​​of character education in the form of (1) hard work in the form of parents have a spirit of hard work to meet their children's needs, as well as a child has a spirit of hard work to achieve his own goals, (2) independent in the form of not too dependent on others, (3) discipline in the form of parents training their children about discipline. The child instills a disciplined attitude in his daily life, (4) nationalist in the form of a child who continues to excel and become superior, and (5) religious in the form of always praying before doing something.